2016
DOI: 10.1038/srep39656
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting bone fragility with human amniotic mesenchymal stem cells

Abstract: The impaired maturation of bone-forming osteoblasts results in reduced bone formation and subsequent bone weakening, which leads to a number of conditions such as osteogenesis imperfecta (OI). Transplantation of human fetal mesenchymal stem cells has been proposed as skeletal anabolic therapy to enhance bone formation, but the mechanisms underlying the contribution of the donor cells to bone health are poorly understood and require further elucidation. Here, we show that intraperitoneal injection of human amni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 40 publications
3
28
0
4
Order By: Relevance
“…However an extensive body of research has shown that in many cases the differentiating cell is multipotent. These findings have been exploited to develop therapies in which one conveniently isolated stem cell population can be used to treat numerous damaged tissues [2,3]. As such, it is assumed that stem cells make a direct cellular contribution to the regenerated tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However an extensive body of research has shown that in many cases the differentiating cell is multipotent. These findings have been exploited to develop therapies in which one conveniently isolated stem cell population can be used to treat numerous damaged tissues [2,3]. As such, it is assumed that stem cells make a direct cellular contribution to the regenerated tissue.…”
Section: Introductionmentioning
confidence: 99%
“…One particularly attractive source is amniotic fluid derived stem cells (AFSCs). These cells support the regeneration of bone [2], lung [16], kidney [17,18], intestine [4], heart [19] and skeletal muscle [20,21]. They are easily isolated from human amniotic fluid which is routinely collected during clinical prenatal diagnostic procedures such as amniocentesis and which is not associated with any ethical issues.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are cells that can be isolated from bone marrow. When being used to treat Osteogenesis Imperfecta the cells form osteoblasts within the body [19]. These osteoblasts will then be able to produce new bone cells within the body.…”
Section: Types Of Stem Cellsmentioning
confidence: 99%
“…These osteoblasts will then be able to produce new bone cells within the body. MSCs have the potential to differentiate into osteoblasts, the type of cells that are responsible for new bone formation [19]. MSCs also have certain characteristics that make them ideal for use in a clinical setting [19].…”
Section: Types Of Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation